4D Printed Multifunctional Composites with Cooling‐Rate Mediated Tunable Shape Morphing. (19th July 2022) - Roach, Devin J.; Sun, Xiaohao; Peng, Xirui; Demoly, Frédéric; Zhou, Kun; Qi, Hang Jerry
Abstract: Multifunctional composites can accomplish multiple tasks such as shape morphing, sensing, and load bearing using a single structure. Smart materials including liquid crystal elastomers (LCE) and shape memory polymers (SMP) have long been used as the primary components of multifunctional composites because of their shape and property changes in response to external stimuli. However, LCEs can generate rapid and reversible shape changes but are soft and require a constant temperature to retain their deformed shape; SMPs have favorable mechanical properties but few can achieve reversible actuations. Moreover, both LCEs and SMPs have limited capability for tunable shape morphing. Multi‐material 3D printing of smart materials, also known as 4D printing, has seen significant advances enabling the fabrication of composites with novel functionality. In this work, 4D printing is leveraged to create an LCE‐SMP composite that can achieve not only rapid and reversible shape changes, but also cooling‐rate regulated tunable shape morphing. The latter is achieved by harnessing the distinct time‐dependent thermomechanical properties of LCEs and SMPs. Furthermore, the composite has a high stiffness at low temperature to support heavy loads. The LCE‐SMP composite hence offers a novel approach to achieve tunable shape morphing for future engineering applications. Abstract : The 4D printing of a novel smart composite is demonstrated comprising of a liquid crystal elastomer and a shape memory polymer. The composite can be reversibly actuated between cooling‐rate tuned stable states with high mechanical stiffness by controlling the cooling rate during actuation.